Mengungkap Identitas Sosial Iklan Komersial Bank Panin Dan Iklan Religius Dompet Dhuafa - Yuliansyah, Hendy (PANTUN: Jurnal Ilmiah Seni Budaya, 2016)
Advertising as it faces a state of society, can be understood as an easy way to get to know in brief social identity. With a variety of a!ributes imposed in an ad, then the level of maturity, life style as well as the vision of a society can be portrayed. Commercial advertising Panin Bank offers ease in all types of banking transactions, which raises the need for new base. While advertisement designed by DompetDhuafa offers the easy way how to do the belief in Islam, and this is the ultimate key of all religious advertising of Dompet Dhuafa. So that the vision in all advertisement of Dompet Dhuafa is how to increase awareness of Moslem in Islamic teaching with zakat or shadaqah.Keywords: advertise, commercial, religious